Tunable third-order nonlinear optical effect via modifying Ti4(embonate)6 cage-based ionic pairs. Issue 9 (22nd March 2022) - Chen, Guang-Hui; He, Yan-Ping; Wang, Zi-Rui; Li, Qiao-Hong; Ma, Zhi-Zhou; Zhang, Jian
Abstract : The integration of Ti4 L6 (L = embonate) cages and various N, N -chelated transition-metal cations into tightly packed structures accurately leads to high-performance materials with adjustable nonlinear optical (NLO) effects. Abstract : Benefiting from the strong inherent π-conjugation properties, the integration of Ti4 L6 (L = embonate) cages and various N, N -chelated transition-metal cations into tightly packed structures accurately leads to high-performance materials with adjustable nonlinear optical (NLO) effects. These cage-based ionic pairs possess different supramolecular packing structures, including a π⋯π stacked porous framework where the Ti4 L6 cages are tactically located at the channels. Interestingly, by introducing the large π-conjugated 1, 10-phenanthroline type ligands and adjusting the aromatic ring electron cloud density, we have effectively regulated their third-order NLO properties, realizing nonlinear absorption responses from reverse saturated absorption (RSA) to saturated absorption (SA). This work not only presents an extraordinary coordination cage-based assembly, but also provides new insights into the function of cage materials.